Psycho-Cardiological Disease: A Bibliometric Review From 2001 to 2021 - You, Yaping; Shou, Xintian; Zhang, Xuesong; Fan, Shaowei; Chai, Ruoning; Xue, Wenjing; Hu, Yuanhui; He, Qingyong (Frontiers in Cardiovascular Medicine, 2022)
The aim is to gain insight into the progress and dynamics of research in the field of psycho-cardiological disease and to track its hot spots, we have analyzed psycho-cardiological disease related literature extracted from the Web of Science core collection from 2001 to 2021 with the help of Cite Space. As a result, 5,032 records were included. Then we can analyze related networks for country, author, subject category, keywords and cited reference. The findings can be summarized to four aspects. Firstly, the annual quantitative distribution of publications is on the rise on the whole, although there is a little slight drop. Secondly, in terms of country analysis, the USA, England, Australia, Germany and Italy are the main research forces in the field of psycho-cardiological diseases, at the same time several academic entities represented by Andrew Steptoe and ROLAND OF KAENELMD have been formed based on the early consciousness of physical and mental health in these countries. Besides, China is also more concerned about it due to the rapid population aging process and the largest population. Thirdly, psycho-cardiological disease is multidisciplinary, including psychology, psychiatry, clinical medicine such as cardiovascular system and neurology, public environmental and occupational health, pharmacology and so on. At the last, the results of keyword analysis and co-cited references indicate that the hotspots in the field of psycho-cardiological disease contain three elements, one is the psychosocial risk factors having come to prominence as a risk factor in the field of psycho-cardiological disease, the second is the focus on the target population such as the elderly, Alzheimer's disease dementia caregivers and cancer patients, and the last is interventions such as exercise therapy and diet therapy. And evaluation methods such as systematic reviews and meta-analyses, covid-19 populations, cardiac rehabilitation, and healthy behaviors are the frontiers of current research. Together these results provide important insights into psycho-cardiological disease and can provide potential collaborators for relevant research workers, as well as current research hotspots and cutting-edge knowledge.